The Catholic Church in Kenya: Transitional Period (Hekima Review, 1993)
A transition period as a rule concerns or deals with handing over responsibility, i.e. authority and leadership on one hand, and accepting the same on the other hand. This may involve phasing out or phasing in. It is a difficult period and can be problematic on both sides.